The Role of Parkin in Rat Pancreatic Beta Cells Fate: Is Parkin more than a ubiquitin kinase? - Verdi, Hasibe; Baysan Cebi, Hatice Pinar; Yilmaz Yalcin, Yaprak; Ozkan, Tulin; Akcil Ok, Mehtap; Sunguroglu, Asuman; Atac, Fatma Belgin (Cellular and Molecular Biology, 2023)
Parkin is a member of the mitochondrial quality control system that plays a major role in mitophagy. Although the loss of function mutations in the Parkin gene has been associated with the Familial Parkinson’s phenotype, research in recent years points out that Parkin’s function is not limited to neurodegenerative diseases. Parkin’s function impressing key cellular quality control mechanisms, including the ubiquitin-proteasome and autophagy-lysosome systems, makes it an important player in the maintenance of cellular homeostasis. In this study, we investigated whether Parkin affects cell viability and ER stress responses under lipotoxic conditions in INS-1E cells. Our results may suggest that silencing Parkin may affect autophagy in addition to apoptosis. We also showed that Parkin may have a protective effect against lipo-toxic effects in INS-1E cells. Consistent with previous studies, we observed that stress responses were different for high and low palmitic acid doses. The Parkin being inhibited under high-dose PA treatment and active under low-dose PA treatment indicate that regulation of stress responses is controlled by environmental conditions. Our preliminary findings may suggest that in low lipotoxic conditions, Parkin affects the ER stress response by modulating Chop activity and Ca2+ release from the ER to the cytoplasm.